The Linguistic Landscape of UAE Schools - Sherazi, Noor Hassan (2024)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Noor Hassan Sherazi entitled, “The Linguistic Landscape of UAE Schools”, submitted in May 2024. Thesis advisor is Dr. Neslihan Bilikozen and thesis co-advisor is Dr. Ozgur Parlak. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).